PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHANMASALAH PESERTA DIDIK - Denil Nilam Sari (Jurnal Edukasi dan Penelitian Matematika, 2018)
One of the goals of learning mathematics is to mathematical problem solving. Mathematical problem solving is the basis for students in understanding mathematics well. But in fact, the ability of problem solving mathematics VIII class  for SMP Negeri 1 Padang still needs to be improved. Solution to solve this problem is problem based learning. The result of the research show that the mathematical problem solving ability of students using model of problem based learning is better than the mathematical problem solving ability of students using conventional learning model. Keywords – mathematical problem solving, problem based learning, conventional learning.